2020
DOI: 10.3390/joitmc6010014
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multimarket Competition on Innovation Strategy: Evidence from the Korean Mobile Game Industry

Abstract: Multimarket contact (MMC) refers to the situation in which more than two firms simultaneously compete with each other in multiple products and/or geographical markets. Most studies on MMC have explored how the market overlap creates “mutual forbearance”, which lessens the intensity of rivalry. While prior studies have mainly focused on how reduced rivalry from MMC influences market-related decisions, only a few have paid attention to its impact on innovation activities. The purpose of this research is to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Given the extensive work that has been undertaken in previous studies to address the relationship between competition and SME innovation (Aghion et al., 2018 ; Cabanelas et al. , 2019; Lee et al. , 2020), it is surprising this is not more developed in the family firm literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the extensive work that has been undertaken in previous studies to address the relationship between competition and SME innovation (Aghion et al., 2018 ; Cabanelas et al. , 2019; Lee et al. , 2020), it is surprising this is not more developed in the family firm literature.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study extends the ongoing debate on the innovative behaviour of family firms to an under-explored but noteworthy aspect-the impact of external stimuli via market competition processes. Given the extensive work that has been undertaken in previous studies to address the relationship between competition and SME innovation (Aghion et al, 2018;Cabanelas et al, 2019;Lee et al, 2020), it is surprising this is not more developed in the family firm literature. This study responds to Park et al's (2019) call to complement knowledge gaps at the intersection of the external environment and family business research fields by exploring the role of market competition in inhibiting or facilitating innovative activity in family businesses.…”
Section: Innovation In Family Owned and Managed Firmsmentioning
confidence: 99%
“…Measuring the loyalty level of its customers guides the companies for providing better and exceptional services. If these services are equipped with innovative ideas it may lead toward sustainable growth which ultimately contribute in the innovative ecosystem [30,67]. It was done through users' loyalty and marketing management where marketing engagement was further subdivided into innovative, functional, emotional, and communal engagement.…”
Section: Discussionmentioning
confidence: 99%
“…They found that there was a positive relationship between R&D intensity and industrial concentration in the corn seed market. With respect to a possibility of lower competition caused by the higher industrial competition, the finding from Lee et al [24] might give an insight that the lower competition could affect the choice of decisions for innovation or R&D across different stages of innovation.…”
Section: Literature Reviewmentioning
confidence: 99%